A 'socialist' economy in a capitalist world. Issue 1 (2nd January 2016) - Golley, Jane
Abstract : Contending views about the 'threats' and 'opportunities' relating to China's economic rise reflect the complex and, for many, confusing role of the state in China's reform and development process. This in turn relates to a marked difference between China's official perception of 'Socialism with Chinese characteristics' and alternative views regarding the nature of its emerging capitalist system. This glaring gap in perceptions is problematic in an increasingly globalised world, complicating debates about what China should and will do to rebalance its domestic economy how other nations should and will react to the recent surge in Chinese investment overseas. This paper reflects on these debates in the context of China's multifaceted and ever-evolving economic system.